INTRANASAL ADMINISTRATION - ANDREASSEN Ole A; QUINTANA Daniel S; MAHMOUD Ramy A; SHELDRAKE Colin David; SMERUD Knut T; WESTLYE Lars T; DJUPESLAND Per Gisle (2025)
A delivery device for and method of modulating a condition relating to social cognition and/or behaviour in a human subject using oxytocin, non-peptide agonists thereof and/or antagonists thereof, comprising : providing a nosepiece to a first nasal cavity of the subject; and providing a supply unit for administering less than 241 U of oxytocin, non-peptide agonists thereof and/or antagonists thereof through the nosepiece to an upper region posterior of the nasal valve which is innervated by the trigeminal nerve. La presente invención se refiere a un dispositivo de suministro para y un método de modulación de una condición relacionada con la cognición y/o comportamiento social en un sujeto humano mediante el uso de oxitocina, agonistas no peptídicos de la misma y/o antagonistas de la misma, que comprende: proporcionar un aplicador nasal a una primera cavidad nasal del sujeto; y proporcionar una unidad de suministro para administrar menos de 24IU de oxitocina, agonistas no peptídicos de la misma y/o antagonistas de la misma a través del aplicador nasal a una región superior posterior de la válvula nasal la cual es inervada por el nervio trigémino.